The potential impact of the christian library in the community: an analysis of the christian community of the Evangelical Church Assembly of God in Maceió (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
This work analyzes the informational need and implementation of a specialized library in relation to Christian literature. The research investigates the possibility of implanting a Christian Public Library in the Christian community in the state of Alagoas, aiming to provide a support environment for specialized educational growth in this area. The thematic approach adds importance to Christian values, cultural and social qualifications, contributing to spiritual, social and scientific growth. The methodology used was bibliographical and documentary, with a qualitative approach. In addition to addressing the Christian information need, the Christian library promotes access to materials relevant to the Christian faith, strengthening the local community.
Keywords: information need; public library; implementation of specialized library; christian literature